Dampak Kewarganegaraan Ganda Bagi Warga Indonesia - Lala Anggina Salsabila; Putri Handayani; Siti Anisah Nasution; Syarifa Aini; Bryan Yamolala Ndruru; Rahmat Fitra; Fazli Rachman (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
In Indonesia, every individual has the right to citizenship status, as regulated in Article 28D Paragraph 4 of the 1945 Constitution which states that "every person has the right to citizenship status." Even though Law Number 12 of 2006 concerning Citizenship of the Republic of Indonesia in principle does not recognize dual citizenship, several legal experts and activists have proposed that Indonesia provide protection for mixed marriage families by implementing the principle of dual citizenship. This article aims to determine the impact of dual citizenship on Indonesian citizens. The research method used is a qualitative approach with library study data analysis techniques. Conceptually, dual citizenship can be interpreted narrowly and broadly. In a narrow sense, dual citizenship refers to the concept of dual citizenship (dual citizenship/nationality) in the status of a person who has two citizenships from two different countries. In a broad sense, dual citizenship is expanded not only to dual citizenship, but also to more than multiple citizenships (plural/multiple citizenship/nationality). In general, dual citizenship can arise due to the application of the principles of citizenship in terms of reciprocal birth (interplay), between the principles of jus sanguinis and jus soli or the naturalization of a citizen of one country to another country.